2014
DOI: 10.1037/a0037597
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographically recalled emotional states impact forward gait initiation as a function of motivational direction.

Abstract: The impact of self-generated affective states on self-initiated motor behavior remains unspecified. The purpose of the current study was to determine how self-generated emotional states impact forward gait initiation. Participants recalled past emotional experiences (anger, fear, happy, sad, and neutral), "relived" those emotional memories before gait initiation (GI), and then walked ∼4 m across the laboratory floor. Kinetic and kinematic data revealed GI characteristics consistent with a motivational directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 77 publications
3
31
0
Order By: Relevance
“…These findings are also in line with studies examining gait initiation after the presentation of positive and negative stimuli (e.g., Bouman and Stins, 2018). These studies show, for example, a faster forward gait initiation when participants recalled autobiographical emotional memories related to happiness compared to emotional memories related to sadness (e.g., Fawver et al, 2014), faster step velocity when walked toward pleasant pictures with positive emotional content compared to unpleasant pictures with negative emotional content (Naugle et al, 2010) and a slower forward step initiation when angry faces are presented in front of them than when smiling faces were presented (Stins and Beek, 2011).…”
Section: Emotional Events Induce Directional Steps In Line With Approsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are also in line with studies examining gait initiation after the presentation of positive and negative stimuli (e.g., Bouman and Stins, 2018). These studies show, for example, a faster forward gait initiation when participants recalled autobiographical emotional memories related to happiness compared to emotional memories related to sadness (e.g., Fawver et al, 2014), faster step velocity when walked toward pleasant pictures with positive emotional content compared to unpleasant pictures with negative emotional content (Naugle et al, 2010) and a slower forward step initiation when angry faces are presented in front of them than when smiling faces were presented (Stins and Beek, 2011).…”
Section: Emotional Events Induce Directional Steps In Line With Approsupporting
confidence: 88%
“…This is an important aspect because, for example, it could be plausible for the word "love" or "unfriendly" to stimulate different mental representations depending on personal experiences (e.g., Niedenthal et al, 2009). Moreover, it has been shown that recalling positive or negative personal life experiences may induce gait patterns in line with approachavoidance behaviors (e.g., Fawver et al, 2014). Along with this notion, concepts that have personal affective values would be good candidates for examining whether their processing also resonates with movements of the whole body.…”
Section: Valence Associations Across the Lateral Space: The Affectivementioning
confidence: 99%
“…Under pleasant stimuli, such as joyful videos/images, increased COP movement was observed during the anticipatory postural adjustment phase of GI [47], [49], [50]. At the same time, an increase in the velocity of the first step [47], [50] and the step length is observed [49], [50]. Similar to happiness, anger resulted in increased COP movement, gait speed, and step length, and posterior-lateral displacement of COP.…”
Section: A Mapping Gait Characteristics To Emotionsmentioning
confidence: 90%
“…This phase is divided into a movement preparation and a movement execution period [51]. Furthermore, the Center of Pressure (COP), representing the point of the ground reaction force vector, has been identified as a key measure of neuromuscular control during GI [47], [49], [50].…”
Section: Discriminative Gait Featuresmentioning
confidence: 99%
See 1 more Smart Citation